Impact of Anchor Borrowers Programme (ABP) on Smallholder Rice Farmers in Kebbi State, Nigeria - Gona, Ayuba; Abubakar Maikasuwa , Muhammad; Kaka, Yahaya (International Journal of Applied and Scientific Research, 2023)
The study examined the impact of Anchor Borrowers Programme on smallholder rice farmers in Kebbi State, Nigeria. A multi stage sampling technique was used to select 500 beneficiary and non-beneficiary rice farmers each giving a sample size of 1000 farmers for the study. Data collected were analysed using Descriptive statistics such as percentages, frequency distribution, performance indices computation, t-test, Chow-test and production function analysis. The results of the analysis of the Chow F computation indicated that there is a significant difference in the production function of beneficiaries and non-beneficiaries respectively since the computed Chow F value of 21.128 was greater than that of the critical F- value at the 0.01 probability level. This is an indication that the ABP performed well. The results further revealed that the two groups of rice farmers were not operating on the same production function. ABP significantly and positively affected output and income of the beneficiary farmers in the study area. It is recommended that Policies should be tailored towards inclusiveness of more farmers into the ABP. The programme should also be extended to cater for other sub-sectors of the Agricultural sectors such as Livestock and Aquaculture.